IMPROVING THE ABILITY OF PRIVATE SCHOOL TEACHERS IN MAKING SCIENTIFIC WRITING THROUGH STRUCTURED ASSISTANCE - Sylvia Rabbani; Rizki Pebriana; Agni Muftianti (PrimaryEdu : Journal of Primary Education, 2018)
In this study the problem arises because of several things as follows: 1). The limited ability of prospective elementary school students to make scientific papers; 2). The limitation of lecturers in processing learning subjects is the technique of writing scientific papers as teaching material. These limitations are feared to cause stagnation in the ability of prospective primary school teachers to make scientific papers. Mentoring is a way to overcome problems that can be caused by reduced availability, support, and guidance of lecturers as adults in the lives of many students. The results of this study are that there is an increase in the ability of prospective elementary school students to make scientific papers with structured mentoring. By implementing structured mentoring in the Scientific Writing Technique course, prospective elementary school teacher students are guided to make scientific papers in a structured manner. The quality of scientific papers made by students of prospective elementary school teachers using structured assistance is quite good. This is because students are structured guided to write scientific papers ranging from finding problems to finding solutions and putting them in scientific papers.